Forensic science and expert testimony in wrongful convictions: a study of decision-making at the criminal cases review commission - Hoyle, Carolyn (The British journal of criminology, 2019)
The Criminal Cases Review Commission reviews possible wrongful convictions in England, Wales and Northern Ireland, referring back to the Court of Appeal cases where there is a ‘real possibility’ that the conviction is unsafe. This article presents findings from a four-year empirical study of decision-making within the Commission. It explores how Commission staff exercise their discretionary powers in identifying and investigating possible wrongful convictions from approximately 1,400 applications a year, referring just a few back to the Court. It focuses on a sample of cases that turned on forensic evidence and expert testimony, showing that while there is some variation in individual caseworkers’ approaches to investigation, decision-making is shaped by the law and internal policies such that reasonably consistent decision frames emerge.